Decision Support System Determines the Best Nutritional Health Study Program at the College of Health Sciences Using the Method TOPSIS (Case Study: Kopertis Region I North Sumatra): Dewi Wahyuni, Dinur Syahputra, Subhan Hafiz Nanda Ginting, M. Rhifky Wayahdi - Dewi Wahyuni; Dinur Syahputra; Subhan Hafiz Nanda Ginting; M. Rhifky Wayahdi (INFOKUM, 2021)
Nutritional health problems now and in the future mean increasing Indonesia's human development index which is still minimal, nutrition graduates are needed who are able to manage nutrition programs from planning to strong evaluation. The need for nutritional health graduates can be seen from the tendency to increase the number of enthusiasts in the field of nutritional health studies, which is still minimal. So prospective students need the best nutritional health study program to make it easier for prospective students to determine the best nutritional health study program at STIKES to be selected. The number of methods in solving problems in decision making such as AHP, SAW, WP, and others.